1885 Nev. Stat. 51 - (:unkn) unknown (My University, 1885)
Ch. 51, § 1: Every person under the age of twenty-one (21) years who shall wear or carry any dirk, pistol, sword in case, slung shot, or other dangerous or deadly weapon concealed upon his person, shall be deemed guilty of a misdemeanor,§
Keywords: CARRY - CONCEALED - MINORS